Psychophysiological stress response of physiotherapy last year students in his final degree dissertation (2020)
Final dissertation is considered one of the most stressful situations in university studies, but the stress response and its incidence in academic achievement is poor knowledge. The aim of the present research was to analyze the effect of the psychophysiological stress response of physiotherapy last year students in his final degree dissertation performance. We analyzed the heart rate variability (HRV) of 110 volunteers during their final degree dissertation to evaluate the autonomic stress response. Results showed a large anticipatory anxiety response of students prior to the final degree dissertation and a no habituation response, since low HRV results were found before and during the final degree dissertation. Only after the dissertation, the HRV increased. No relationship between autonomic modulation and the dissertation academic achievement were found. Final degree dissertation in physiotherapy students, produce a large anticipatory anxiety response. Autonomic modulation parameters do not present relationship with the final degree dissertation performance.